KELAYAKAN HUTAN RAKYAT DALAM SKEMA PERDAGANGAN KARBON : KAWASAN HUTAN RAKYAT KAMPUNG CALOBAK, DESA TAMANSARI, KECAMATAN TAMANSARI, KABUPATEN BOGOR, PROPINSI JAWA BARAT - Fahmi Hakim; Haryanto R. Putro; Hariadi Kartodihardjo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2011)
The rate of Indonesian forest destruction caused by deforestation and forest degradation contribute greatly to climate change and global warming. Development of Community Forest could be potential in carbon sequestration and then go into Carbon Trading Scheme. Initiative to get the incentives for the management of Community Forests through carbon trading in the voluntary carbon market is a concrete step to participate in the adaptation and mitigation of climate change and gain maximum benefit from the ecosystem of the forest resources. Thus, based on the guidelines of LEI certification decision, the Calobak community forest management get the title of